Oral 5‐aminosalicylic acid for maintenance of remission in ulcerative colitis - Wang, Yongjun (Cochrane Database Syst Rev, 2016)
BACKGROUND: Oral 5‐aminosalicylic (5‐ASA) preparations were intended to avoid the adverse effects of sulfasalazine (SASP) while maintaining its therapeutic benefits. Previously, it was found that 5‐ASA drugs were more effective than placebo but had a statistically significant therapeutic inferiority relative to SASP. This updated review includes more recent studies and evaluates the effectiveness, dose‐responsiveness, and safety of 5‐ASA preparations used for maintenance of remission in quiescent ulcerative colitis. OBJECTIVES: The primary objectives were to assess the efficacy, dose‐responsiveness and safety of oral 5‐ASA compared to placebo, SASP, or 5‐ASA comparators for maintenance of remission in quiescent ulcerative colitis. A secondary objective was to compare the efficacy and safety of once daily dosing of oral 5‐ASA with conventional (two or three times daily) dosing regimens. SEARCH METHODS: A literature search for relevant studies (inception to 9 July 2015) was performed using MEDLINE, EMBASE and the Cochrane Library. Review articles and conference proceedings were also searched to identify additional studies. SELECTION CRITERIA: Studies were accepted for analysis if they were randomized controlled trials with a minimum treatment duration of six months. Studies of oral 5‐ASA therapy for treatment of patients with quiescent ulcerative colitis compared with placebo, SASP or other 5‐ASA formulations were considered for inclusion. Studies that compared once daily 5‐ASA treatment with conventional dosing of 5‐ASA and 5‐ASA dose ranging studies were also considered for inclusion. DATA COLLECTION AND ANALYSIS: The primary outcome was the failure to maintain clinical or endoscopic remission. Secondary outcomes included adherence, adverse events, withdrawals due to adverse events, and withdrawals or exclusions after entry. Trials were separated into five comparison groups: 5‐ASA versus placebo, 5‐ASA versus sulfasalazine, once daily dosing versus conventional dosing, 5‐ASA versus comparator 5‐ASA formulation, and 5‐ASA dose‐ranging. Placebo‐controlled trials were subgrouped by dosage. Once daily versus conventional dosing studies were subgrouped by formulation. 5‐ASA‐controlled trials were subgrouped by common 5‐ASA comparators (e.g. Asacol and Salofalk). Dose‐ranging studies were subgrouped by 5‐ASA formulation. We calculated the risk ratio (RR) and 95% confidence intervals (95% CI) for each outcome. Data were analyzed on an intention‐to‐treat basis. MAIN RESULTS: Forty‐one studies (8928 patients) were included. The majority of included studies were rated as low risk of bias. Ten studies were rated at high risk of bias. Seven of these studies were single‐blind and three studies were open‐label. However, two open‐label studies and four of the single‐blind studies utilized investigator performed endoscopy as an endpoint, which may protect against bias. 5‐ASA was significantly superior to placebo for maintenance of clinical or endoscopic remission. Forty‐one per cent of 5‐ASA patients relapsed compared to 58% of placebo patients (7 studies, 1298 patients; RR 0.69, 95% CI 0.62 to 0.77). There was a trend towards greater efficacy with higher doses of 5‐ASA with a statistically significant benefit for the 1 to 1.9 g/day (RR 0.65; 95% CI 0.56 to 0.76) and the > 2 g/day subgroups (RR 0.73, 95% CI 0.60 to 0.89). SASP was significantly superior to 5‐ASA for maintenance of remission. Forty‐eight per cent of 5‐ASA patients relapsed compared to 43% of SASP patients (12 studies, 1655 patients; RR 1.14, 95% CI 1.03 to 1.27). A GRADE analysis indicated that the overall quality of the evidence for the primary outcome for the placebo and SASP‐controlled studies was high. No statistically significant differences in efficacy or adherence were found between once daily and conventionally dosed 5‐ASA. Twenty‐nine per cent of once daily patients relapsed over 12 months compared to 31% of conventionally dosed patients (8 studies, 3127 patients; RR 0.91, 95% CI 0.82 to 1.01). Eleven per cent of patients in the once daily group failed to adhere to their medication regimen compared to 9% of patients in the conventional dosing group (6 studies, 1462 patients; RR 1.22, 95% CI 0.91 to 1.64). There does not appear to be any difference in efficacy among the various 5‐ASA formulations. Forty‐four per cent of patients in the 5‐ASA group relapsed compared to 41% of patients in the 5‐ASA comparator group (6 studies, 707 patients; RR 1.08, 95% CI 0.91 to 1.28). A pooled analysis of two studies showed no statistically significant difference in efficacy between Balsalazide 6 g and 3 g/day. Twenty‐three per cent of patients in the 6 g/day group relapsed compared to 33% of patients in the 3 g/day group (216 patients; RR 0.76; 95% CI 0.45 to 2.79). One study found Balsalazide 4 g to be superior to 2 g/day. Thirty‐seven per cent of patients in the 4 g/day Balsalazide group relapsed compared to 55% of patients in the 2 g/day group (133 patients; RR 0.66; 95% CI 0.45 to 0.97). One study found a statistically significant difference between Salofalk granules 3 g and 1.5 g/day. Twenty‐five per cent of patients in the Salofalk 3 g/day group relapsed compared to 39% of patients in the 1.5 g/day group (429 patients; RR 0.65; 95% CI 0.49 to 0.86). Common adverse events included flatulence, abdominal pain, nausea, diarrhea, headache, dyspepsia, and nasopharyngitis. There were no statistically significant differences in the incidence of adverse events between 5‐ASA and placebo, 5‐ASA and SASP, once daily and conventionally dosed 5‐ASA, 5‐ASA and comparator 5‐ASA formulations and 5‐ASA dose ranging studies. The trials that compared 5‐ASA and SASP may have been biased in favour of SASP because most trials enrolled patients known to be tolerant to SASP which may have minimized SASP‐related adverse events. AUTHORS' CONCLUSIONS: 5‐ASA was superior to placebo for maintenance therapy in ulcerative colitis. However, 5‐ASA had a statistically significant therapeutic inferiority relative to SASP. Oral 5‐ASA administered once daily is as effective and safe as conventional dosing for maintenance of remission in quiescent ulcerative colitis. There does not appear to be any difference in efficacy or safety between the various formulations of 5‐ASA. Patients with extensive ulcerative colitis or with frequent relapses may benefit from a higher dose of maintenance therapy. High dose therapy appears to be as safe as low dose and is not associated with a higher incidence of adverse events.